When Britain Saved the West: The Story of 1940. (March 2016) - Waters, Christopher
Abstract : When Britain Saved the West: The Story of 1940. By Robin Prior (New Haven and London: Yale University Press, 2015), pp.xxi + 335. AU55.00 (cloth), distributed in Australia by Footprint Books.